Evaluation of the Effect of Ginger Zingiber Officinale Extract on Kidney of Albino Rat Administered with Graded Doses of Piroxicam - Uwuigbe Mathew; Ohiwerei Wisdom Omogbai; Ajanwachukwu; Ogbonna Wilson; Edebiri Ogbemudia .E; Loveth Ada Adikwu (MultiTech Publisher, 2025)
Ginger or ginger root is the rhizome of the plant Zingiber officinale, commonly consumed as a delicacy, medicine, or spice. It is named after its genus and belongs to the Zingiberaceae family. Ginger is native to southern China and later spread to the Spice Islands, other parts of Asia, West Africa, and the Caribbean. This study aims to evaluate the effects of ginger Zingiber officinale extracts on the kidney when administered alongside graded doses of piroxicam. Fifty albino rats were used, divided into five (5) equal groups (A to E) of ten (10) rats each. Group A served as the control, while Group B received 2.7mg/kg of piroxicam. Group C was administered 400mg/kg of ginger, Group D received 2.7mg/kg of piroxicam and 100mg/kg of ginger, and Group E received 2.7mg/kg of piroxicam along with 400mg/kg of gingerData on weight changes were analyzed using ANOVA, with statistical significance set at P < 0.05. All results were expressed as Mean ± Standard Error of Mean (SEM) and presented in tables for statistical comparison. However, Group B (administered 2.7mg/kg of piroxicam) displayed signs of renal distortion, while Group C (administered 400mg/kg of ginger) showed adipose tissue formation. Groups D and E, which received both piroxicam and ginger at different doses, exhibited normal histological features. Further research is recommended to determine the precise effects of mild, moderate, and high doses of Zingiber officinale (ginger) on kidneys affected by varying levels of piroxicam